Washington View: "Keep it simple, stupid" sometimes is too simple. (November 2015) - Ferguson, Maria
Keeping it simple as a design concept is certainly laudable, but the American education system is far too complex for several of the proposed and popularized solutions to actually work. Donald Trump's simple solution of expelling all persons who illegally entered the U.S. and the Obama administration's plan to evaluate teachers based on student test scores both fail by quite a lot, although they seem simple ways to address education problems .